(untitled) (Biological Sciences - PJSIR, 2000)
Studies on heterosis were carried out in five intraspecific hybrids of tetraploid cotton Gossypium hirsutum L. All hybrids manifested positive heterosis over mid-parent and control variety Qalandri regarding yield per plant. The extent of heterosis recorded was 60.2% and 94.3% over mid-parent and check variety Qalandri respectively. For boll weight the heterosis ranged from -1.52 to + 49.5%, for plant height from -7.40 to + 39.22%, for sympodia per plant from + 0.99 to + 2.70% and for staple length from + 1.82 to + 4.0%.